Efficacy of PARP inhibitors in advanced high-grade serous ovarian cancer according to BRCA domain mutations and mutation type - Buonaiuto, Roberto; Neola, Giuseppe; Caltavituro, Aldo; Longobardi, Alessandra; Mangiacotti, Federica Pia; Cefaliello, Amedeo; Lamia, Maria Rosaria; Pepe, Francesco; Ventriglia, Jole; Malapelle, Umberto; Troncone, Giancarlo; Giuliano, Mario; et al. (Frontiers in Oncology, 2024)
ObjectivePreclinical studies have emphasized the potential connection between BRCA specific domains defects and the activity of Poly ADP-ribose polymerase inhibitors (PARPi). Nevertheless, real-world evidence regarding the impact of BRCA domain defects and mutations on PARPi efficacy are limited. The aim of his study was to evaluate the efficacy of PARPi in terms of progression free survival (PFS) according to BRCA domains defects and mutation types.MethodsA retrospective analysis was performed among 79 BRCA mutated patients, diagnosed with advanced High-grade serous ovarian carcinoma (HGSOC) who received first- and second-line platinum- based chemotherapy followed by PARPi maintenance treatment. PFS was evaluated according to BRCA1 [Really Interesting Gene (RING), DNA Binding (DBD), Serine Cluster (SCD), BRCA1 C-terminal (BRCT)] and BRCA2 [RAD-51 Domain (RAD-51 BD), DBD] specific domain defects and mutation types [missense (MS), nonsense (NS), frameshift (FS), splicing (S), or large rearrangements (LR)].ResultsAfter a median follow-up of 51 months, no significant difference in PFS was observed between the BRCA functional domains or mutation types in the BRCA1 and BRCA2 subgroups. Patients with BRCA2 DBD and RAD51-BD defects had the longest (39.8 months) and shortest (24.1 months) median PFS, respectively (p = 0.11). Additionally, patients with BRCA1 DBD defects had the greatest benefit (median PFS = 33.8 months) while those with BRCA1 RING domain mutations experienced the worst outcome (median PFS = 30.9 months (p = 0.43).ConclusionThe efficacy of maintenance treatment with PARPi is independent by BRCA domain defects or mutation types. Patients DBD domain defects experienced numerically longer median PFS compared to those with other BRCA1/2 alterations.